Cross-Border Governance in the Euroregions at the External Borders of the European Union - Valentina CORNEA (ACROSS)
In cross-border cooperation processes, the stakeholder defines their objectives and how they can act. Subsequent actions are carried out according to forces and capacities, which articulate a political-administrative vision oriented towards the achievement of these objectives. The study analyses and identifies the way to achieve the cross-border cooperation objectives in the Euroregions at the external borders of the European Union. Using a cross-border institutional mapping tool, the development process of cross-border governance is described based on five evolutionary processes - knowledge creation, relationship articulation, decision-making, implementation, management, and outcome evaluation. The results of the study allow defining the typologies of cross-border actors and institutions and the levels in which they are involved. Cross-border governance, explained in empirical and contextual terms highlights the fact that the achievement of the assumed objectives oscillates depending on the nature of the actors' own capacities, the power relations within the region, as well as the geo-political context.